Mali : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix briefly surveys the progress achieved by Mali in the area of economic adjustment in the decade since 1988. This is followed by a discussion of the principal areas where the Malian government is considering the implementation of new reforms in the period ahead. The paper analyzes the financial sector in Mali. It highlights that in the late 1980s, the financial sector, in particular the banking system, faced a major liquidity and solvency crisis characterized by a high level of nonperforming loans.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet